2020
DOI: 10.3390/cancers13010099
|View full text |Cite
|
Sign up to set email alerts
|

Association between Growth Differentiation Factor-15 (GDF-15) Serum Levels, Anorexia and Low Muscle Mass among Cancer Patients

Abstract: The pathophysiology of cancer anorexia is complex and serum biomarkers, including growth and differentiation factor(s) (GDF), may be modulated. We explored the association(s) between GDF-15 serum levels and anorexia and, secondarily, with low muscle mass and body weight loss in cancer patients. We considered gastrointestinal and lung cancer patients (CP) and healthy BMI-matched controls. The FAACT-questionnaire was administered to diagnose anorexia and we calculated the L3-SMI by CT scan to assess low muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…The possible role of inflammation in the pathogenesis of muscle loss in SSc patients deserves speculation. Indeed, systemic inflammation is a potent driver of muscle loss in a number of both acute (e.g., ICU) and chronic (e.g., cancer) conditions [7,39,40]. In the present study, both the inflammatory indices CRP and ESR were not significantly different between the low and normal FFMI groups.…”
Section: Discussioncontrasting
confidence: 47%
“…The possible role of inflammation in the pathogenesis of muscle loss in SSc patients deserves speculation. Indeed, systemic inflammation is a potent driver of muscle loss in a number of both acute (e.g., ICU) and chronic (e.g., cancer) conditions [7,39,40]. In the present study, both the inflammatory indices CRP and ESR were not significantly different between the low and normal FFMI groups.…”
Section: Discussioncontrasting
confidence: 47%
“…Mean circulating GDF-15 levels have been suggested to be higher in patients with pancreatic ductal adenocarcinoma, as 1731 pg/mL [ 23 ], 2428 [ 24 ], 7694.58 [ 1 ] and 2990.2 (this study), compared to patients with colorectal adenocarcinoma (CRC) (1371.0 pg/mL [ 23 ] and 2030 pg/mL [ 25 ]), non-small-cell lung carcinoma (mean, 1258.0 pg/mL [ 23 ] and median, 828.8–2000 pg/mL [ 34 , 35 ]), and gastric adenocarcinoma (1154.0 pg/mL [ 23 ]). An atlas of the human transcriptome reported that GDF-15 mRNA expression was relatively low in pancreatic cancer compared to prostate, urothelial, renal, melanoma, and colorectal cancers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that patients in the high-GDF-15 group experienced severe appetite loss compared with those in the low-GDF-15 group. In a previous study, median serum GDF-15 levels were higher in cancer patients with anorexia (1224.1 pg/mL) than in patients without anorexia (812.4 pg/mL) [ 34 ], where the cut-off value for anorexia was set at the lowest Functional Assessment of Anorexia/Cachexia Treatment (FAACT) score tertile, similar to the consensus definition of anorexia (FAACT ≤ 24) [ 38 ]. Our results showed that median MDASI scores in the high- and low-GDF-15 groups were 4 and 1 on a 0–10 scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, association between GDF15 level and weight loss was only confirmed in patients with lung but not pancreatic cancer [ 33 ]. Additionally, another study found no difference in GDF15 levels between cancer patients with weight loss and those without weight change [ 35 ]. This study demonstrated an association between GDF15 levels and anorexia, suggesting that it could be an biomarker for anorexia rather than cachexia [ 35 ].…”
Section: Cachexia-inducing Factorsmentioning
confidence: 99%